What do Parents Learn by Reading a DPT Vaccine Information Form? - Ronald Gold; Gordean L Bjornson (Canadian Journal of Infectious Diseases)
Objective: Information forms are commonly used to inform parents about childhood vaccination. This study assessed the knowledge of mothers about pertussis and pertussis vaccine before and after reading a form about diphtheria-pertussis-tetanus (dpt) vaccine.